Kurdish EFL Students’ Perceptions towards Summative and Formative Assessment at Salahaddin University - Mahmood, Salar Khalid; Ghaleb, Nawsha (Journal of Tikrit University for Humanities, 2024)
Inappropriate choice of assessment type in education may undermine the positive facets of both the teaching and learning process. The assessment system at Salahaddin University-Erbil has remained in an unchanged form over a prolonged duration. The students at Salahaddin University think that the assessment system fails to help them improve their learning process. Hence, the current assessment system should undergo certain changes. This study aims to delve into Kurdish EFL students’ perceptions of summative and formative assessment at Salahaddin University and look for ways to refine the existing assessment framework to better address students’ needs and contribute to the improvement of their overall learning experience. Additionally, it aims to pinpoint which assessment type yields a more positive impact on both the teaching practices and students’ learning. A mixed-methods approach has been adopted to attain the aims of the study. Quantitative data was obtained by administering a survey questionnaire to 542 students majored in English language across three Colleges at Salahaddin University to capture their perceptions about the two forms of assessment. Qualitative data has been gathered through interviewing thirty senior English majors at three colleges within Salahaddin University to quest for solutions to the problems that they encounter with the current assessment system. Results yield promising conclusions by showing that the students at Salahaddin University are not satisfied with the assessment system in use at the present time because they believe that it has a detrimental impact on their academic achievement. According to their beliefs, the assessment system needs to be altered towards a more formative-oriented style since it opens threads for helping them enhance their learning experience and equips them for the demands of the labor market competently. Results prove beneficent as they provide significant information for the board of trustees and faculty staff of Salahaddin University who are in charge of refining the assessment framework, which consequently leads to the improvements of the educational structure and the overall quality of both teaching and learning.